2009
DOI: 10.1186/1472-6750-9-94
|View full text |Cite
|
Sign up to set email alerts
|

Non-antibiotic selection systems for soybean somatic embryos: the lysine analog aminoethyl-cysteine as a selection agent

Abstract: BackgroundIn soybean somatic embryo transformation, the standard selection agent currently used is hygromycin. It may be preferable to avoid use of antibiotic resistance genes in foods. The objective of these experiments was to develop a selection system for producing transgenic soybean somatic embryos without the use of antibiotics such as hygromycin.ResultsWhen tested against different alternate selection agents our studies show that 0.16 μg/mL glufosinate, 40 mg/L isopropylamine-glyphosate, 0.5 mg/mL (S-(2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…A similar low concentration of chlorsulfuron (10 nM) has previously been found to effectively inhibit transgenic rice protoplast growth (Li et al 1992). On the other hand, chlorsulfuron-resistant maize calli were selected on 50 nM chlorsulfuron, while soybean embryos were only sensitive to ALS herbicides (mix of primisulfuron and prosulfuron) when a concentration as high as 183 mg/l was applied (Fromm et al 1990; Rao et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…A similar low concentration of chlorsulfuron (10 nM) has previously been found to effectively inhibit transgenic rice protoplast growth (Li et al 1992). On the other hand, chlorsulfuron-resistant maize calli were selected on 50 nM chlorsulfuron, while soybean embryos were only sensitive to ALS herbicides (mix of primisulfuron and prosulfuron) when a concentration as high as 183 mg/l was applied (Fromm et al 1990; Rao et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Paz et al (2006) used the cotyledonary node of half-seeds as an explant and reported 1.4-8.7% transformation efficiency. Recently, Rao et al (2009) reported the selection of soybean somatic embryos on non-antibiotic selection medium as lysine-insensitive dihydrodipicolinate synthase gene with non-antibiotic selection agent S-(2-aminoethyl)-Lcysteine.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results in our lab showed that this marker/agent can also efficiently select transgenic somatic embryos (unpublished results). Rao et al . (2009) successfully developed a system to select somatic embryos using the E. coli dap A gene, which confers resistance to glufosinate, glyphosate, S-(2 aminoethyl)-L-cysteine and imidazolinones.…”
Section: Selection Systemmentioning
confidence: 99%